Adiponectin: Potential Protein Hormone as a Candidate Biomarker for Male Fertility - H Hafizuddin; Ni Wayan Kurniani Karja; Lisa Praharani; Mohamad Agus Setiadi (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Reproduction is an important factor that requires attention to increase livestock production. The application of artificial insemination (AI) technology has been developed rapidly in the world, so that availability of fertile superior male is a determinant factor of successful AI. Several recent studies have been aimed to discover male fertility biomarker, by intense research on fertility-associated proteins contained in seminal plasma. This paper describes the role of adiponectin as a biomarker candidate of male fertility. Adiponectin has a positive effect on spermatozoa functionality and steroidogenesis. This has been proven by several studies that found its expression in Sertoli cells and Leydig cells in the reproductive tract. Based on the specific role on spermatozoa functionality and steroidogenesis in supporting male fertility parameter, it is strongly suggested that adiponectin is an excellent candidate biomarker for male fertility.